Living in a Hostile World: Inflammation, New Drug Development, and Coronavirus - Dobson, Geoffrey P.; Biros, Erik; Letson, Hayley L.; Morris, Jodie L. (Frontiers in Immunology, 2021)
We present a brief history of the immune response and show that Metchnikoff’s theory of inflammation and phagocytotic defence was largely ignored in the 20th century. For decades, the immune response was believed to be triggered centrally, until Lafferty and Cunningham proposed the initiating signal came from the tissues. This shift opened the way for Janeway’s pattern recognition receptor theory, and Matzinger’s danger model. All models failed to appreciate that without inflammation, there can be no immune response. The situation changed in the 1990s when cytokine biology was rapidly advancing, and the immune system’s role expanded from host defence, to the maintenance of host health. An inflammatory environment, produced by immune cells themselves, was now recognized as mandatory for their attack, removal and repair functions after an infection or injury. We explore the cellular programs of the immune response, and the role played by cytokines and other mediators to tailor the right response, at the right time. Normally, the immune response is robust, self-limiting and restorative. However, when the antigen load or trauma exceeds the body’s internal tolerances, as witnessed in some COVID-19 patients, excessive inflammation can lead to increased sympathetic outflows, cardiac dysfunction, coagulopathy, endothelial and metabolic dysfunction, multiple organ failure and death. Currently there are few drug therapies to reduce excessive inflammation and immune dysfunction. We have been developing an intravenous (IV) fluid therapy comprising adenosine, lidocaine and Mg2+ (ALM) that confers a survival advantage by preventing excessive inflammation initiated by sepsis, endotoxemia and sterile trauma. The multi-pronged protection appears to be unique and may provide a tool to examine the intersection points in the immune response to infection or injury, and possible ways to prevent secondary tissue damage, such as that reported in patients with COVID-19.